The burden of household out-of-pocket healthcare expenditures in Ethiopia: a systematic review and meta-analysis - Moges Tadesse Borde; Robel Hussen Kabthymer; Mohammed Feyisso Shaka; Semagn Mekonnen Abate (BMC, 2022)
Abstract Background In Ethiopia, household Out-Of-Pocket healthcare expenditure accounts for one-third of total healthcare expenditure, is one of the highest in the world, and still creates barriers and difficulties for households to healthcare access and may delay or forgo needed healthcare use. Despite the presence of a few highly dispersed and inconsistent studies, no comprehensive study was conducted. Therefore, in this systematic review and meta-analysis, we aimed at estimating the pooled estimates of the burden of household Out-Of-Pocket healthcare expenditures among Ethiopian households and identifying its determinants. Methods We systematically searched articles from PubMed / Medline and Google scholar databases and direct Google search engine without restriction on publication period. Cross-sectional and cohort articles and grey literature published in English were included. Data were extracted using Microsoft Excel. Two reviewers screened the titles, reviewed the articles for inclusion, extracted the data, and conducted a quality assessment. The third reviewer commented on the review. Articles with no abstracts or full texts, editorials, and qualitative in design were excluded. To assess quality, Joanna Briggs Critical Appraisal Tools was used. A Forest plot was used to present summary information on each article and pooled common effects. Potential heterogeneity was checked using Cochrane's Q test and I-squared statistic. We checked publication bias using a Funnel plot. Moreover, subgroup and sensitivity analyses were performed. Meta-analysis was used for the pooled estimates using RevMan statistical software Version 5.4.1. Results In this review, a total of 27 primary articles were included (with a total sample size of 331,537 participants). Because of the presence of heterogeneity, we employed a random-effects model; therefore, the pooled burden household Out-Of-Pocket / catastrophic healthcare expenditure in Ethiopia was strongly positively associated with household economic status. The odds of facing Out-Of-Pocket / catastrophic healthcare expenditures among the poorest quintile was about three times that of the richest (AOR = 3.09, 95% CI: 1.63, 5.86) p-value < 0.001. In addition, on pooled analysis, the mean direct Out-Of-Pocket healthcare expenditures were $32 per month (95%CI: $11, $52) (SD = $45), and the mean indirect Out-of-Pocket healthcare expenditures were $15 per month (95%CI: $3, $28) (SD = $17). The mean catastrophic healthcare expenditure at 10% of threshold was also disproportionately higher: 40% (95%CI: 28, 52%) (SD = 20%). Moreover, the common coping mechanisms were a sale of household assets, support from family, or loan: 40% (95%CI: 28, 52%) (SD = 20%). Conclusion Our study revealed the evidence of inequity in financial hardship that the burden of household Out-Of-Pocket / catastrophic healthcare expenditures gap persists among Ethiopian households that is unfair and unjust. To reduce the detected disparities in seeking healthcare among Ethiopian households, national healthcare priorities should target poor households. This calls for the Ministry of Health to improve the challenges and their impact on equity and design better prepayment policies and strengthen financial protection strategies to protect more vulnerable Ethiopian households. Protocol registration The details of this protocol have been registered on the PROSPERO database with reference number ID: CRD42021255977 .